Imaging of Extracellular pH Using Hyperpolarized Molecules. Issue 9 (12th June 2017) - Hundshammer, Christian; Düwel, Stephan; Schilling, Franz
Abstract: Many diseases can overrule natural pH regulatory mechanisms and alter the extracellular pH (pHe ). A non‐invasive method that resolves pHe in vivo with high spatial and temporal resolution could therefore improve diagnosis and monitoring of diseases, contributing to the concept of precision medicine. During the last decades, several techniques have been proposed to image pHe non‐invasively. The majority of these methods rely on magnetic resonance because of its good spatial resolution, high penetration depth, non‐ionizing radiation and excellent complimentary soft tissue contrast. Dissolution dynamic nuclear polarization (DNP) is an emerging concept to enhance nuclear magnetic resonance (NMR) signals by more than four orders of magnitude, making it possible to observe in vivo metabolic processes in real‐time. Here, we summarize and review recent developments in pHe imaging techniques based on hyperpolarization methods and give an overview of recently discovered hyperpolarized pH sensor molecules that have been applied in vitro and in vivo . Abstract :